Optimum plot size for experiments with the sunflower - Sousa, Roberto; Silva, Paulo Sérgio; Assis, Janilson; Silva, Paulo Igo; Silva, Júlio César (Revista Ciência Agronômica, 2014)
The aim of this study was to determine a suitable plot size for field experiments with the sunflower. An experiment was carried out in a randomised complete block design with 14 sunflower cultivars and 10 replications. The plots consisted of four rows, six metres in length, spaced 0.7 m apart with 0.3 m between plants. The working area of the plot (7.56 m2), consisting of the two central rows, was divided into 12 basic units, each consisting of three plants per row (0.63 m2), from where the yield of the sunflower seeds was obtained. Suitable plot size was estimated using the intraclass correlation coefficient method. The detectable difference between treatments was also estimated (d). The optimum plot size for the evaluation of grain yield in the sunflower was 2.52 m2 (working area), considering a boundary of one row on each side. Greater gains in experimental precision (16%) with increases in plot size, occurred up to eight basic units (5.04 m2) using seven replications. Increasing the number of replications and the plot size was more efficient in increasing experimental precision, than increasing the number of cultivars.